Dampak Modal Kerja Terhadap Nilai Perusahaan Pada Perusahaan Subsektor Makanan dan Minuman di Bursa Efek Indonesia - Ahmad, Rukia; Junus, Onong; Rahman, Zubaidah (CV. Dalle’ Deceng Abeeayla, 2025)
This research aims to determine the impact of working capital on firm value. This is a quantitative study that explains the relationship or influence between variables. The sample used consists of 30 companies over the period 2018-2022, with 150 financial report data points. This research uses secondary data obtained from the annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange. The data analysis method used in this research is multiple linear regression. The independent variables in this research are the working capital structure and working capital turnover. The dependent variable in this research is firm value. Based on the analysis results, it shows that, simultaneously, working capital turnover and working capital structure do not affect firm value.